Microbial Tracking of Multidrug-Resistant Klebsiella Pneumoniae Isolates in a Pediatric Hospital Setting. (April 2013) - Bernaschi, P.; Del Chierico, F.; Petrucca, A.; Argentieri, A.; Atti, M. Ciofi Degli; Ciliento, G.; Carletti, M.; Muraca, M.; Locatelli, F.; Putignani, L.
We investigated the clonal relatedness of seven multi-drug-resistant (MDR) Klebsiella pneumoniae isolates, as well as three susceptible K. pneumoniae isolates collected during hospital outbreaks and outbreak-related microbiological surveillance, respectively. The relatedness among K. pneumoniae isolates was assessed by pulsed field gel electrophoresis (PFGE) and automated repetitive-sequence-based PCR (rep-PCR) genotyping and the results were compared to a proteomic phenotyping performed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). All typing methods agreed on the generation of three different clusters of K. pneumoniae isogenetic/related MDR strains. After strengthening hospital infection control measures, no other spreading events involving MDR- K. pneumoniae were reported until the end of the observation period. This preliminary investigation suggests that, in a hierarchical approach to bacterial typing, MALDI-TOF MS proteome profiling might offer a fast and valuable preliminary screening tool able to support microbiologists during nosocomial outbreak surveys.